Decision-Making While Passing and Visual Search Strategy During Ball Receiving in Team Sport Play. Issue 2 (April 2020) - Natsuhara, Takayuki; Kato, Takaaki; Nakayama, Masao; Yoshida, Takuya; Sasaki, Ryota; Matsutake, Takahiro; Asai, Takeshi
In many team sports, in which environmental change is constant, athletes selectively allocate attention between the approaching ball and other players, and constantly consistently making decisions regarding whom to pass the ball to. Few previous studies on decision-making in team sports such as soccer have included the ball reception phase. This study examined players' visual search strategies during pass decisions. Using five-on-four soccer-specific film simulations from previously recorded real scenes, high-level players (HLPs) and middle-level players (MLPs) reacted to life-sized soccer scenes. We measured their visual search strategies in decision-making tasks involving ball reception and pass execution and collected their verbal reports. We employed a novel system wherein the ball is ejected toward participants according to the video clips in order to maintain perception–action coupling during the task. We found skill-based differences in decision-making accuracy, eye movement data, and verbal reports. HLPs demonstrated better decision-making than MLPs, and, in eye movement data, HLPs allocated more attention to nonmarked attackers ([ M ] = 14.1, [ SD ] = 4.8%, p < .001, η 2 = 0.39), the teammate receiving the pass ( M = 18.4, SD = 4.3%, p < .05, η 2 = 0.15), and opponents ( M = 14.6, SD = 6.3%, p < .05, η 2 = 0.17) than did MLPs. Furthermore, according to verbal reports, HLPs tended to attend to information on opponent players. Thus, visual search strategies during ball reception suggest that the position and situation of teammates and opponents are the most important information sources for accurate and consistent pass decisions.